Examining a WeChat-supported 5E-flipped classroom pedagogical approach. (14th June 2019) - Hew, Khe Foon; Tang, Ying; Lo, Chung Kwan; Zhu, Yanzhen
The use of flipped classroom has gained widespread interest among many universities in recent years. Yet, despite this interest, we still lack specific guidance on how to structure the pre-class and in-class activities in a conceptually coherent way to engage students. Using an educational modelling language (orchestration graphs), we illustrate a flipped classroom design that incorporates the use of 5E instructional phases and a mobile instant messaging tool (WeChat). We implemented this WeChat-supported 5E flipped classroom approach in two master-level graduate classes, namely E-Learning Strategies and Engaging Adult Learners involving a total of 48 students. A mixed-method approach was utilised to collect quantitative and qualitative data from student surveys, and student interviews and instructor reflections. Results suggested a majority of participants found the flipped classroom approach to be more engaging than the traditional method. We also discussed the benefits and challenges of using WeChat along four different axes: 1) interactivity vs. distraction; 2) immediacy vs. pressure; 3) abundancy vs. disorganisation; 4) intimacy vs. detachment.